Adsorption of Chromium (VI) with Silica Coated on Iron Sand Magnetic Material Modified with Propyldiethylenetriamine - Susanto, Susanto; Prasdiantika, Ricka (Politeknik Negeri Malang, 2024)
Chromium metal ions with an oxidation number of six (Cr (VI)) were heavy metals that are toxic and harmful to the environment that pollute the environment from industrial waste, so efforts are needed to overcome the metal ion waste. In this study has been tested a silica coated on iron sand magnetic material modified with propyldiethylenetriamine to adsorb heavy metal of Cr (VI) on pH variation, adsorbate concentration variation, and time variation. The research was started with the preparation of iron sand magnetic material with an external magnet, activation of iron sand magnetic material with HCl solution, silica coating by propyldiethylenetriamine group on the batch system, silica-propyldiethylenetriamine coating on iron sand magnetic material using sol-gel method, and adsorption process to Cr (VI) was performed at pH variation 5–7, adsorbate concentration 200-500 ppm, and contact time 30–180 min. The results showed that the adsorbent of silica coated on iron sand magnetic material modified with propyldiethylenetriamine made capable of adsorption Cr (VI). The optimum condition of adsorption occurs at pH 6, contact time 60 min with a concentration of Cr (VI) at 400 ppm. At optimum conditions, adsorbent of silica coated on iron sand magnetic material modified with propyldiethylenetriamine has the ability to adsorb metal ions chromium (VI) of 81.09% with adsorbed 324.34 ppm from initial concentration 400 ppm.